MEASURING THE QUALITY OF LIFE OF OLDER PEOPLE: DEVELOPMENT OF AN INSTRUMENT. (11th November 2018) - Darvishpoor Kakhki, A; Davidson, P
Abstract: The elderly are the fastest growing segment of the population globally and this is pronounced in developing countries such as Iran. Optimizing quality of life is a key goal for active ageing. This study was describes the development of an instrument for measuring quality of life of older people in Tehran, Iran. The methodology proceeded in sequential steps. In-depth interviews and a comprehensive literature review were undertaken for item generation. Following thematic analysis six sub-scales were identified: absence of disease, autonomy, mental health, family integrity, social participation, and spiritual well-being. The questionnaires were administered to a representative sample of 400 community-dwelling older people who had referrals to elderly centers in Tehran. Then, psychometric methods were used to assess the validity and reliability of the instrument. The results of the content validity index and assessment by experts suggested good content and face validity. Factor analysis yielded the five a priori factors of social participation (9 items), family integrity (8 items), spiritual well-being (6 items), autonomy (6 items), and absence of disease (11 items). 26 items that showed a minimum loading and inappropriate meanings with factors were excluded. The reliability analysis of 50 items in the six sub-scales showed satisfactory results (Cronbach's alpha and test-retest reliability ranged from 0.83 to 0.96). The instrument of Quality Of Life of Older People (QOL-OP) is valid, reliable, concise, easy to complete, and can be effectively applied for measuring quality of life of older people.